Pengaruh Media Sosial, Modernitas, Dan Kualitas Layanan Online Terhadap Minat Beli : (Survei Terhadap Pengguna Marketplace Shopee Pada Mahasiswa Jurusan Manajemen Angkatan 2018-2021 Universitas Perjuangan Tasikmalaya) - Rifki Agung Pratama (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
The purpose of this research is to measure and determine the effect of social media, modernity, and quality of online services on buying interest (Survey of Shopee Marketplace Users on Management Department Students Class of 2018-2021 Universitas Perjuangan Tasikmalaya). This study uses a quantitative approach to survey methods, the population in this study is students from the Department of Management, Faculty of Economics and Business, Universitas Perjuangan Tasikmalaya, amounting to 1,229 students. This sample collection uses Probability Sampling using a Simple Random Sampling approach to 302 students. The data used in the form of primary data, in determining the number of samples the researchers used the Slovin formula and 5% as the level of error. In collecting data the researchers used a questionnaire. The analytical tool used with the help of SPSS 25.0, based on the results of the study showed that based on the correlation analysis of social media, modernity, and online service quality had a moderate influence on buying interest partially social media did not have a significant effect on buying interest, partially modernity and The quality of online services has a significant effect on buying interest. Simultaneously, social media, modernity, and the quality of online services have a significant effect on buying interest.